CHYDENANTHUS MIERS (LECYTHIDACEAE): A CORRECTION - Kartawinata, Kuswata (REINWARDTIA, 1984)
In my article on the genus ChydenmUhus Miers in Reinwardtia 10 (1) : 28, 1982, I stated that "the genus, like Barringtouia and Abdid-majidia, has one- seeded fruit". This statement is partially wrong. Abdulmajidla fruit has 2-5 seeds, the main reason that the genus was established (Kochumen in Hit.